Optimization of Flow Rate Distribution in a Crude Oil Preheat Train Considering Fouling Deposition in Shell and Tube Sides - Carvalho, Carolina Borges de; Carvalho, Esdras Penêdo de; Ravagnani, Mauro Antônio da Silva Sá (Industrial & engineering chemistry research, 2022)
The deposition of an undesired material on the heat transfer surfaces is a recurrent problem that affects the overall performance of heat exchanger networks (HENs). A wide variety of empirical and semiempirical models are available for predicting the fouling behavior. In this work, there are considered different predominant fouling mechanisms at each side of the shell and tube heat exchangers used to preheat crude oil from a refinery. Adopting the mass flow rates at the parallel branches of the HEN as optimization variables, an optimization model is proposed to find the minimum total annual cost for 12 months of uninterrupted operation. The model was coded in MATLAB and solved using a simulated annealing algorithm. The results showed that fouling accumulation in both heat exchanger sides significantly impacted the heat recovery and increased operating costs. The proposed methodology was able to decrease the total annual cost in $4.6516 × 104 when compared to the base case.